ECHO 9 infection in pregnant women with suspected rubella. Issue 4 (April 1975) - Bell, E J; Ross, C A; Grist, N R
Abstract : Both rubella virus and Echovirus 9 (ECHO 9) were epidemic in Scotland during the summer of 1973; both viruses can cause a mild febrile illness with rash. Sera from 286 rubella-negative pregnant women were tested for neutralizing antibodies to ECHO 9 virus; 40 women had antibody titres suggestive of recent infection. Prospective studies on the outcome of these pregnancies are in progress but preliminary results suggest no connexion between fetal damage and ECHO 9 infection.